Pengenalan Internet dan Jaringan Serta Pembuatan Kabel Unshielded Twisted Pair (UTP) pada Mahasiswa Universitas Muhammadiyah Jambi - Helmina Helmina; Rian Dani; Trie Hierdawati; Siswoyo Siswoyo; Rika Neldawaty (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Community Service Activities in the form of internet and network training as well as Making Unshielded Twisted Pair (UTP) Cables for Muhammadiyah Jambi University Students aims to increase students' knowledge of network technology and the benefits of the internet as well as encouraging students to be able to independently manage networks and the internet. The training method used is a form of training outside the classroom using lecture, discussion and question and answer methods as well as direct networking practice. The lecture method used is intended to provide a theoretical explanation of internet and network material. The discussion method is used to explore students' understanding of the material given in lectures. The practical method is used to show directly how to make Unshielded Twisted Pair (UTP) cables. The benefits gained from this training activity are that students are able to make network connections with Unshielded Twisted Pair (UTP) cables and know the benefits of the internet.